2012
DOI: 10.1097/jom.0b013e31824fe192
|View full text |Cite
|
Sign up to set email alerts
|

Long Working Hours and Cardiovascular Disease

Abstract: These findings provide evidence of increased CVD with long working hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 45 publications
0
34
2
3
Order By: Relevance
“…9, 18 Kang et al (2012) reported a 37 percent increase in the odds of CVD among those exposed to long work hours (the definition of which varied by study) compared to those unexposed (95% CI: 1.11 – 1.70), which was not influenced by age, geographical location, or study year. A subgroup analysis of participants working ≤55 hours per week attenuated the relationship between work hour duration and CVD (OR: 1.28; 95% CI: 0.85 – 1.91).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9, 18 Kang et al (2012) reported a 37 percent increase in the odds of CVD among those exposed to long work hours (the definition of which varied by study) compared to those unexposed (95% CI: 1.11 – 1.70), which was not influenced by age, geographical location, or study year. A subgroup analysis of participants working ≤55 hours per week attenuated the relationship between work hour duration and CVD (OR: 1.28; 95% CI: 0.85 – 1.91).…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup analysis of participants working ≤55 hours per week attenuated the relationship between work hour duration and CVD (OR: 1.28; 95% CI: 0.85 – 1.91). 18 Virtanen et al (2012) demonstrated that working long hours (definition varied by study) was associated with an estimated 80 percent increase in the risk of CVD (RR: 1.80; 95% CI: 1.42 – 2.29). In a series of subgroup analyses, they reported that studies defining LWH as a threshold above 50 WH/w had substantially higher RRs than those studies defining LWH as a threshold equal to or below 50 WH/w (RR≤50 WH/w: 1.41; 95% CI: 1.14 – 1.74 vs. RR>50WH/w: 2.37; 95% CI: 1.56 – 3.59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our results shows significant associations only in longest working-hour group, these results are in line with those of previous studies, which reported an association between long working hours and CHD. A meta-analysis study concluded that longer working hours was related with the risk of CHD with an OR of 1.37 [14]. Another meta-analysis of 4 prospective studies reported a relative risk of 1.39 for long working hours on CHD [4].…”
Section: Discussionmentioning
confidence: 99%
“…Noise and vibration have been studied mostly separately without adjustment for other occupational factors related to the CVD, such as occupational smoke and dust [19], heavy lifting [20], extreme temperatures [21], working hours [22] and shift work [23]. Furthermore, the evidence from Bulgaria is largely insufficient, outdated, and lacks adequate adjustments of the models to draw conclusions about the risk nowadays.…”
mentioning
confidence: 99%